1994
DOI: 10.1007/bf02331618
|View full text |Cite
|
Sign up to set email alerts
|

Chronic back pain and work disability: Vocational outcomes following multidisciplinary rehabilitation

Abstract: Studies indicate that work disabled chronic back pain patients out of work for longer than three months have a reduced probability of returning to work. The escalating personal and economic costs (indemnity and health care) associated with such long term disability have facilitated efforts at multiple levels to prevent and more effectively manage work disability. Multidisciplinary rehabilitation (MDR) targeted at return to work represents one such approach. The approach is based upon a multidimensional concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…9,31,33 In addition to time off work and gender, we found that small amounts of variance in RTW were related to differences in performance of IWS-FCE lifting subtests. Although greater trunk force and leg force have each been associated with improved RTW, 34 our study is the first to show that the greater the lifting ability the greater the likelihood of RTW.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…9,31,33 In addition to time off work and gender, we found that small amounts of variance in RTW were related to differences in performance of IWS-FCE lifting subtests. Although greater trunk force and leg force have each been associated with improved RTW, 34 our study is the first to show that the greater the lifting ability the greater the likelihood of RTW.…”
Section: Discussionmentioning
confidence: 83%
“…38 A review of several studies that used RTW as an outcome variable following rehabilitation for low back pain 9 showed that RTW is a multi-determinant outcome that often was not well defined and included several types of vocational outcomes. Because RTW is so important for individuals with disabilities and for the institutions that provide disability benefits, some authors 9,36,38 recom- There were limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 16 articles (56-71) were included by screening the references of the retrieved studies and of reviews about back schools (6,7,72), pain treatment centers (73)(74)(75), occupational rehabilitation (8,76) and spinal manipulation (9,10).…”
Section: Resulfsmentioning
confidence: 99%
“…It is important to explore the characteristics of what factors allow for the persistence of employment despite functional limitations. Whereas several studies, including some meta analyses (10)(11)(12) have explored the factors that address the duration of the absence from work following injury, particularly, the factors that lead to application for retirement or disability benefits, little work has been completed on those individuals with limitations who are working prior to the development of a chronic illness or injury.…”
Section: Introductionmentioning
confidence: 99%